Improving Knowledge of Oral and Dental Health in Parents of Elementary School Children Through ‘Gigi Sehat' Video Channel - Ramadhani, Aulia; Raharyani, Hillary Desiree (Faculty of Dental Medicine Universitas Airlangga, 2020)
Background: Dental caries is one of the dental and oral health problems found the most in children. A previous study in Surabaya has revealed a high prevalence of dental caries in pre-school children (67.5%) resulting in a high severity level (def: 7.0). It occurred because of the poor mother's knowledge of dental and oral health. It could be due to poor efforts to access information about oral and dental health which significantly affects child dental care. Studies show mothers in Surabaya mostly used Youtube as one of the media for accessing the information on the internet (46.2%). In Surabaya, the percentage of mothers having smartphones for accessing the internet was high (91.6%). Purpose: This study aimed to find out the effectiveness of the Youtube channel in improving parents' knowledge about dental and oral health. Methods: This study was observational descriptive research using a cross-sectional study design. Thirty samples were selected through the total sampling of the population of parents in one of the elementary schools in Surabaya, Indonesia. This study employed pre-test and post-test methods to measure an increase in knowledge level. The participants' knowledge was assessed before and after they were briefed and asked to watch Youtube videos regularly for 4 weeks. Data collected were then analyzed by the paired T-Test comparison test in SPSS. Results: In the pre-test, the participants' knowledge about dental and oral health was at a 65% level. While the post-test showed an increase in their knowledge into 93%. There was a significant difference between the two results (p < 0.05). Conclusion: Educative video channels on dental and oral health can effectively improve parents' knowledge about dental and oral health.